Cancer risks for PMS2-Associated lynch syndrome - Ten Broeke, Sanne W.; Knebel Doeberitz, Magnus von (Journal of clinical oncology, 2018)
PurposeLynch syndrome due to pathogenic variants in the DNA mismatch repair genes MLH1, MSH2, and MSH6 is predominantly associated with colorectal and endometrial cancer, although extracolonic cancers have been described within the Lynch tumor spectrum. However, the age-specific cumulative risk (penetrance) of these cancers is still poorly defined for PMS2-associated Lynch syndrome. Using a large data set from a worldwide collaboration, our aim was to determine accurate penetrance measures of cancers for carriers of heterozygous pathogenic PMS2 variants.MethodsA modified segregation analysis was conducted that incorporated both genotyped and nongenotyped relatives, with conditioning for ascertainment to estimates corrected for bias. Hazard ratios (HRs) and corresponding 95% CIs were estimated for each cancer site for mutation carriers compared with the general population, followed by estimation of penetrance.ResultsIn total, 284 families consisting of 4,878 first- and second-degree family members were included in the analysis. PMS2 mutation carriers were at increased risk for colorectal cancer (cumulative risk to age 80 years of 13% [95% CI, 7.9% to 22%] for males and 12% [95% CI, 6.7% to 21%] for females) and endometrial cancer (13% [95% CI, 7.0%-24%]), compared with the general population (6.6%, 4.7%, and 2.4%, respectively). There was no clear evidence of an increased risk of ovarian, gastric, hepatobiliary, bladder, renal, brain, breast, prostate, or small bowel cancer.ConclusionHeterozygous PMS2 mutation carriers were at small increased risk for colorectal and endometrial cancer but not for any other Lynch syndrome-associated cancer. This finding justifies that PMS2-specific screening protocols could be restricted to colonoscopies. The role of risk-reducing hysterectomy and bilateral salpingo-oophorectomy for PMS2 mutation carriers needs further discussion.
Gesehen am 09.05.2019